2011
DOI: 10.1097/aln.0b013e31820c2b81
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure of the Anesthesiologist in the Neurointerventional Suite

Abstract: Background: Scatter radiation during interventional radiology procedures can produce cataracts in participating medical personnel. Standard safety equipment for the radiologist includes eye protection. The typical configuration of fluoroscopy equipment directs radiation scatter away from the radiologist and toward the anesthesiologist. This study analyzed facial radiation exposure of the anesthesiologist during interventional neuroradiology procedures. Methods: Radiation exposure to the forehead of the anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…A previous study reported that anaesthetists are exposed to 6.5 AE 5.4 lSv per procedure, more than three times greater than radiologists, during neuroradiological procedures [10]. Several studies have reported radiation exposure among vascular surgeons involved in fluoroscopy-assisted surgery [14][15][16], and found exposure to be within safe recommended limits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that anaesthetists are exposed to 6.5 AE 5.4 lSv per procedure, more than three times greater than radiologists, during neuroradiological procedures [10]. Several studies have reported radiation exposure among vascular surgeons involved in fluoroscopy-assisted surgery [14][15][16], and found exposure to be within safe recommended limits.…”
Section: Discussionmentioning
confidence: 99%
“…The only previous study reported for interventional neuroradiology [10] included 31 patients, and contained no information about radiation exposure during EVAR. Unable to calculate an informed sample size, we selected a convenience sample in excess of 30 patients per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found low lens doses in neurointerventional procedures performed using a ceiling-suspended shield [40]. Efstathopoulos showed that, despite using a ceiling-suspended shield, a radiologist performing vertebroplasty with monoplane fluoroscopy was predicted to exceed the ICRP dose limit at 27.9 mSv/year [27].…”
Section: Quantifying Lens Exposure In Interventional Radiologymentioning
confidence: 98%
“…However, because of the complexity of the pathologies to be treated, there is a significant number of procedures requiring prolonged X-ray procedures or high-dose acquisitions, which can result in increased radiation exposure to the patients as well as staff members [5,6] , leading to potential deterministic and stochastic adverse effects [7] .…”
Section: Introductionmentioning
confidence: 99%